Microbiological identification of genes that have resistance to antibiotics in Staphylococcus aureus - Rodrigues de Melo, Karina Lohaine; Costa, Samara de Alcântara; Janebro, Daniele Idalino; Melo Peixoto, Maria do Socorro Rocha; de Souza Medeiros, Bartolomeu Garcia; Lucena, Valeska Silva (Revista de Ciências Médicas e Biológicas, 2016)
Introduction: the hospital environment favors the acquisition of antimicrobial resistance, being important the aseptic environment and the control of carriers for reducing these infections. Species of Staphylococcus aureus resistant to antibiotics became a cosmopolitan problem due to its degree of virulence and the association with various diseases. These opportunistic microorganisms are usually found in the nasal cavities witch develop rapidly in the asymptomatic patients and, once reaching the hands, may spread rapidly among those patients who are in a state of immunosuppression. Objetive: therefore, this study aimed to identify the presence of antibiotic-resistant Staphylococcus aureus in the nostrils of health professionals in Campina Grande-PB. Methodology: for this purpose, it was collected 50 samples of nasal health professionals who had clinically healthy, with no sign of staphylococcal infection. Results: it was found that 28 of the 50 samples, or 56% were positive for S. aureus, and 12/28 samples (42.86%) were resistant to oxacillin and is therefore considered MRSA. Conclusion: the high levels of S. aureus among health professionals may contribute to the spread of this pathogen among immunosuppressed patients and, therefore, are necessary and essential preventive measures such as hand hygiene and nasal decolonization of MRSA carriers from those with mupirocin.